Challenges of Peer Instruction in an Undergraduate Student-Led Learning Community: Bi-Directional Diffusion as a Crucial Instructional Process - Airliana, Apta Aura (Proceedings Series on Social Sciences & Humanities, 2025)
This journal is entitled Challenges of peer instruction in an undergraduate student-led learning community: bi-directional diffusion as a crucial instructional process. The research paper discusses the benefits and challenges of learning communities (LCs), which offer learners opportunities to engage in authentic learning experiences within real-world or simulated professional communities. The research paper gathered data through interviews, Slack conversations, field notes, and artifacts related to StandUp, a socio-technical system. The study aimed to understand how students and peer-instructors influenced the implementation and advocacy of StandUp within the teams.The study examined the engagement of student leaders in implementing the StandUp practice, revealing unexpected patterns that existing theories could not predict. The findings suggest a bi-directional diffusion process in Student-Led Learning Communities (SLLCs), in which peer-instructors and students mutually influence each other''s decisions to advocate and participate in practices. The paper investigates the instructional processes that emerge when peer-instructors attempt to teach students an authentic project management practice in student-led learning communities (SLLCs). The researchers propose a bi-directional diffusion model to describe instructional processes in SLLCs, highlighting the challenges peer-instructors face in persuading students to engage in disciplinary practices and the influence students have on peer-instructors.